Vitamin D pathway activation selectively deactivates signal transducer and activator of transcription (STAT) proteins and inflammatory cytokine production in natural killer leukemic large granular lymphocytes. (November 2018) - Olson, Kristine C.; Kulling Larkin, Paige M.; Signorelli, Rossana; Hamele, Cait E.; Olson, Thomas L.; Conaway, Mark R.; Feith, David J.; Loughran, Thomas P.
Graphical abstract: Highlights: NKL cell line used as a model for NK cell large granular lymphocyte leukemia. Exogenous IL-2 causes tyrosine phosphorylation in STAT1 through 6 in NKL cells. NKL co-treated with IL-2 and calcitriol (vitamin D) or EB1089 (calcitriol analog). Calcitriol or EB1089 deactivate STAT1 and 3 in NKL cells and NK-LGLL patient PBMCs. 15 cytokines significantly altered in NK-LGLL; EB1089 decreased 3 cytokines in NKL. Abstract: Calcitriol, the active form of vitamin D, has been well documented to act directly on immune cells and malignant cells. Activated T cells are one of the best characterized targets of calcitriol, with effects including decreasing inflammatory cytokine output and promoting anti-inflammatory cytokine production. However, the effects of calcitriol on natural killer (NK) cells are less clear. Reports suggest that only immature NK cell populations are affected by calcitriol treatment resulting in impaired cytotoxic function and cytokine production, while mature NK cells may have little or no response. NK cell large granular lymphocyte leukemia (NK-LGLL) is a rare leukemia with CD3-CD16+CD56+NK cell clonal expansion. The current standard treatments are immunosuppressant therapies, which are not curative. The Janus kinase (JAK) – signal transducer and activator of transcription (STAT) pathway is hyperactivated in LGLL and is one pathway of interest in new drug target investigations. We previously demonstrated the ability of calcitriol to decrease STAT1 tyrosine 701 (p-STAT1) and STAT3 tyrosine 705 (p-STAT3) phosphorylation as well as inflammatory cytokine output of T cell large granular lymphocyte leukemia cells, but did not determine the effects of calcitriol on NK-LGLL. Therefore, in the present study, we investigated whether NKL cells, a model of NK-LGLL, and NK-LGLL patient peripheral blood mononuclear cells (PBMCs) are susceptible to treatment with calcitriol or seocalcitol (EB1089), a potent analog of calcitriol. NKL cells are dependent on interleukin (IL)-2 for survival and we show here for the first time that treatment with IL-2 induced tyrosine phosphorylation of STATs 1 through 6. Both calcitriol and EB1089 caused significant upregulation of the vitamin D receptor (VDR). IL-2 induction of p-STAT1 and p-STAT3 phosphorylation was significantly decreased after calcitriol or EB1089 treatment. Additionally, IL-10, interferon (IFN)-γ, and FMS-like tyrosine kinase 3 ligand (Flt-3L) extracellular output was significantly decreased at 100 nM EB1089 and intracellular IL-10 was decreased with either calcitriol or EB1089 treatment. We treated NK-LGLL patient PBMCs with calcitriol or EB1089 and found decreased p-STAT1 and p-STAT3 while VDR increased, which matched the NKL cell line data. We then measured 75 serum cytokines in NK-LGLL patients (n = 8) vs. age- and sex-matched normal healthy donors (n = 8), which is the first serum cytokine study for this LGLL subtype. We identified 15 cytokines, including IL-10 and Flt-3L, which were significantly different between normal donors and NK-LGLL patients. Overall, our results suggest that activating the vitamin D pathway could be a mechanism to decrease STAT1 and 3 activation and inflammatory cytokine output in NK-LGLL patients.